Underground pollution travel from leach pits of on-site sanitation facilities: A case study - Banerjee G. (My University, 2025)
A long-term field study was undertaken under different hydro-geological conditions at some locations of the state of West Bengal (India) to understand the phenomenon of underground pollution movement, and to assess safe horizontal distance of water sources from on-site sanitation leach pits. The study showed that pollution travel from leach pits, both in horizontal and vertical directions, is dependent on soil type, permeability, hydraulic gradient, grain size, and position of groundwater table with respect to the leach pits. A minimum travel of pollutant of 2.055 m was found in clayey silt soil, whereas a maximum travel of 10.20 m was observed in gravel-sand composition of soils in 10-day period. The study also demonstrated that clay envelop around leach pit arrests the movement of pollutant (both chemical and bacteriological) to a considerable extent. In the present study, graphical technique has been suggested for estimating underground travel of bacteriological contamination under given soil composition. © 2010 Springer-Verlag.